2015
DOI: 10.1177/2050640615580889
|View full text |Cite
|
Sign up to set email alerts
|

The association between Helicobacter pylori infection and inflammatory bowel disease based on meta‐analysis

Abstract: The results of this meta-analysis showed a significant negative association between H. pylori infection and IBD that supports a possible protective benefit of H. pylori infection against the development of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 71 publications
(108 reference statements)
9
108
0
3
Order By: Relevance
“…However, findings are varied and, to date, have failed to support a definitive association in IBD (Hold et al, 2014). A recent meta-analysis involving 33 studies that included 4400 IBD patients showed a significant negative association between H. pylori and IBD (Rokkas et al, 2015). Furthermore, a recent cohort study indicated that the organism might be protective against CD development (Bartels et al, 2016).…”
Section: Helicobacter Speciesmentioning
confidence: 99%
“…However, findings are varied and, to date, have failed to support a definitive association in IBD (Hold et al, 2014). A recent meta-analysis involving 33 studies that included 4400 IBD patients showed a significant negative association between H. pylori and IBD (Rokkas et al, 2015). Furthermore, a recent cohort study indicated that the organism might be protective against CD development (Bartels et al, 2016).…”
Section: Helicobacter Speciesmentioning
confidence: 99%
“…A more recent meta-analysis of 33 eligible studies that included 4,400 IBD patients and 4,763 controls (the vast majority being non-Asian) found that 26.5% of IBD patients were H. pylori positive, compared to 44.7% of individuals in the control group. These data resulted in an estimated risk ratio of 0.62 (95% confidence interval: 0.55-0.71, p < 0.001) [76]. In the most recent and most comprehensive meta-analysis to date (which includes studies published until July 2015), with data from 40 studies, CD and UC patients were evaluated together as well as separately [74].…”
Section: Epidemiological Evidence Suggests An Inverse Association Betmentioning
confidence: 99%
“…The compound is ready for the phase III clinical trial. Probiotics and prebiotics may also be included in the treatment so as to normalize the GI microfloral ecosystem [14][15][16][17][18] .…”
Section: Current Treatments Of Gastrointestinal Diseasesmentioning
confidence: 99%
“…The infecting bacteria, or the antibiotics used to eliminate them, may also alter the balance of the indigenous microbiota. Often these problems are overcome on their own with time, but sometimes probiotic supplementation may be needed [10,[14][15][16][17][18] .…”
Section: Microbiota and Gastrointestinal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation